(untitled) (Baghdad Science Journal, 2011)
In this study forty mature albino rats were used wich were randomly divided into five groups ,four groups were adminstrated Phoenix dactylifera pollen grains suspension at concertenrations (18,54,108,and 216)mg/ kg body weight by oral administration while the fifth group was considered as a control group.Experiment continued for 40 days then rats were sacrificed and samples of blood were collected for determination of some biochemical parameters (total protein ,total cholesterol ,LDLc and HDLc).Testis were removed for preparation histological sections to measures the diameters of seminferous tubules ,thickness of seminiferous epithelium and the numbers of spermatogenic cells. Results showed significant increase(p